2012
DOI: 10.1038/nutd.2012.8
|View full text |Cite|
|
Sign up to set email alerts
|

Overweight in singletons compared to children with siblings: the IDEFICS study

Abstract: The aim of this study was to compare the prevalence of overweight in only children to those with siblings and to explore potential behavioral mediating factors. This study relies upon cross-sectional data collected at survey centers in eight European countries participating in Identification and prevention of Dietary- and lifestyle-induced health EFfects In Children and infantS (IDEFICS). The present analysis is based on measured anthropometry and parent or guardian-reported socio-demographic characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
47
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 19 publications
(17 reference statements)
6
47
0
Order By: Relevance
“…Although some previous studies did not found an association between weight status and family composition (47) , Padez et al (7) also found in their cross-sectional study among 7-to 9?5-year-old children that being a single child was significantly associated with overweight in girls. This has also been reported in the past for the UK (48) , the Netherlands (49) and more recently by the IDEFICS Study (Identification and prevention of Dietaryand lifestyle-induced health Effects In Children and infantS) (50) using data of eight European countries. Children without siblings possibly got less PA, had greater sugar consumption and were more likely to have a TV in their bedroom (50) .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although some previous studies did not found an association between weight status and family composition (47) , Padez et al (7) also found in their cross-sectional study among 7-to 9?5-year-old children that being a single child was significantly associated with overweight in girls. This has also been reported in the past for the UK (48) , the Netherlands (49) and more recently by the IDEFICS Study (Identification and prevention of Dietaryand lifestyle-induced health Effects In Children and infantS) (50) using data of eight European countries. Children without siblings possibly got less PA, had greater sugar consumption and were more likely to have a TV in their bedroom (50) .…”
Section: Discussionmentioning
confidence: 82%
“…This has also been reported in the past for the UK (48) , the Netherlands (49) and more recently by the IDEFICS Study (Identification and prevention of Dietaryand lifestyle-induced health Effects In Children and infantS) (50) using data of eight European countries. Children without siblings possibly got less PA, had greater sugar consumption and were more likely to have a TV in their bedroom (50) . This should be kept in mind when developing interventions addressing lifestyle behaviours.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, 12 720 children were included based upon completeness of family structure data (35) . All survey centres obtained ethics approval from their respective authority.…”
Section: Family Structure and Overweightmentioning
confidence: 99%
“…This results is consistent to anothers studies which also found more than risk of EW in singletons. 16,28 This association is explained by the fact of a greater number of children implies a greater division of family income, therefore, singletons would present a greater possibility for acquisition to preferred products with high energetic density. 29 It is emphasized that the excessive mother´s concern with child care and the persistence of the belief that child feeding is directly related to weight gain.…”
Section: Discussionmentioning
confidence: 99%